External and internal training loads for intensive and extensive tactical-conditioning in soccer small sided games - Zanetti, V.; Aoki, M. S.; Bradley, P. S.; Moreira, A. (Journal of Human Kinetics, 2022)
This study aimed to investigate the external (ETLs; 15-Hz GPS unit coupled with a 100 Hz tri-axial accelerometer) and internal training loads (ITLs; session-RPE method) of 18 elite U20 soccer players (19 ± 1.0 years, 178 ± 8 cm, 71 ± 7 kg) undertaking a tactical-conditioning training program with special reference to small-sided games (SSGs). The SSGs used in this program were either extensive (SSG-extensive) or intensive (SSG-intensive) training sessions, that were alternated within the assessed weeks. Tactical principles of the game influenced the aim of the technical-tactical content. Total distance (TDR; ES: 1.17), and a very high-speed running distance (HSR; ES: 0.96) were greater in SSG-extensive vs. SSG-intensive. However, no meaningful difference was found for accelerations (ACC; ES: 0.12) and decelerations (DEC; ES: 0.08). However, a higher perceived intensity (session-RPE; ES: 0.62) and greater ITLs (ES: 0.27) were found for SSG-intensive. These findings suggest that coaches should prescribe SSG training sessions not only considering the usual variables (rules, player numbers, etc.). The current data indicate that the tactical objective of SSGs in relation to exercise bout duration and rest intervals should be considered, while implementing a multi-dimensional training monitoring program during SSG tactical-conditioning training sessions, integrating ETL and ITL variables to gain a better understanding of training responses.